Suzaku observations of the 2013 outburst of KS 1947+300 - Ballhausen, Ralf; Kühnel, Matthias; Pottschmidt, Katja; Furst, Felix; Hemphill, Paul B.; Falkner, Sebastian; Gottlieb, Amy M.; Grinberg, Victoria; Kretschmar, Peter; Kreykenbohm, Ingo; Rothschild, Richard E.; Wilms, Jörn (Astronomy & Astrophysics, 2016)
We report on the timing and spectral analysis of two Suzaku observations with different flux levels of the high-mass X-ray binary KS 1947+300 during its 2013 outburst. In agreement with simultaneous NuSTAR observations, the continuum is well described by an absorbed power law with a cutoff and an additional blackbody component. In addition, we find fluorescent emission from neutral, He-like, and even H-like iron. We determine a pulse period of 18.8 s with the source showing a spin-up between the two observations. Both Suzaku observations show very similar behavior of the pulse profile, which is strongly energy dependent. This profile has an evolution from a profile with one peak at low energies to a profile with two peaks of different widths toward higher energies seen in both the Suzaku and NuSTAR data. Such an evolution to a more complex profile at higher energies is rarely seen in X-ray pulsars, most cases show the opposite behavior. Pulse phase-resolved spectral analysis shows a variation in the absorbing column density, N, over pulse phase. Spectra taken during the pulse profile minima are intrinsically softer compared to the pulse phase-averaged spectrum.
Keywords: Accretion; accretion disks; Pulsars: individual: KS 1947+300; X-rays: binaries